Manipulating drug release from tridimensional porous substrates coated by initiated chemical vapor deposition. Issue 33 (25th April 2019) - Ghasemi‐Mobarakeh, Laleh; Werzer, Oliver; Keimel, Roman; Kolahreez, Davood; Hadley, Peter; Coclite, Anna Maria
ABSTRACT: In the recent years, modern wound dressings have attracted much interest to accelerate wound healing processes with the topical delivery of drugs directly on wounds having a significant effect on wound rehabilitation. The objective of this study was to develop a model dressing that would not only provide wound protection from the environment but might also provide the possibility to keep it moist and deliver a drug for potential speeding the healing process. Poly(ethylene terephthalate), cotton fabrics, and polycaprolactone (PCL) nanofibers were used as different tridimensional porous substrates, loaded with a model drug, clotrimazole. The results show that the chemical structure and surface area to volume ratio of the pristine substrates affect the drug release profile. Coating of such substrates by hydrogels poly(2‐hydroxyethyl methacrylate) (p‐HEMA) and poly(methacrylic acid) (p‐MAA) was successfully achieved by initiated chemical vapor deposition. This method was chosen because it is gentle and solventless and most important it can coat free areas within the three‐dimensional structures. Scanning electron microscopy results revealed that p‐HEMA and p‐MAA conformally coated the fibers of the substrates. Moreover, drug release experiments showed that p‐HEMA and p‐MAA coatings provide barriers preventing sudden drug release. In conclusion, our results indicated the possibility of fabricating dressings containing a drug with tunable drug release profile depending on several parameters even though a strong porous structure exists. © 2019 The Authors. Journal of Applied Polymer Science published by Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47858. Abstract :